Preparation of EG/water mixture-based nanofluids using metal-oxide nanocomposite and measurement of their thermophysical properties - Karakas, Ayse; Harikrishnan, S.; Öztop, Hakan Fehmi (Elsevier, 2022)
The experimental work was carried out to probe the effect of nanocomposite added into ethylene glycol/water (as base fluid) on the thermophysical properties. The nanocomposites to be dispersed into base fluid were produced via the hydrothermal method. The surface morphology, the composition of particles, and the crys-talline structure of the nanocomposites were characterized. Ethylene glycol/water mixtures with different vol-ume ratios were taken into account in the present study. To prepare nanofluids, the nanocomposites with 0.3, 0.6, and 0.9 vol% were dispersed into base fluid using a two-step approach. The effects of nanocomposites in base fluids were studied concerning thermal conductivity, specific heat capacity, and viscosity. Besides, the ther-mophysical properties of the nanofluids were verified with respect to the operating temperature. Considering the results, the newly prepared nanofluids exhibited improved thermophysical properties and hence, this nanofluid can be reckoned to be a potential substitute for conventional fluids at higher temperature applications.
Keywords: EG; water mixture; Nanocomposite; Nanofluids; Specific heat; Thermal conductivity; Viscosity